Examining Mood structures in Chukwuemeka Ike's The Chicken Chasers - KOUTCHADE, INNOCENT SOUROU; DATONDJI, COCOU ANDRÉ; AMADOU, SALAMI (My University, 2019)
This article focuses on the grammar on interpersonal meaning in Chukwuemeka Ike’s The Chicken Chasers through the mood patterns. It aims to use the method drawn from Systemic Functional Linguistics (SFL) to investigate into the language of the writer. To conduct the present research work, we have used the methodological approach of sampling. Thus, two extracts have been selected from the novel under study. The data are analyzed through the linguistic features of mood, modality and adjuncts. The findings reveal that the two extracts display various mood-types as well as features of modality which are modulation and modalization and adjunct features. All these features contribute to the realization of interpersonal function and the understanding of the writer’s language.
Keywords: Mood patterns; interpersonal meaning; Systemic Functional Linguistics (SFL); modality; adjunct